National identities in the context of Shakespeare's Henry V: Exploring contemporary understandings through collocations. (22nd August 2020) - Culpeper, Jonathan; Findlay, Alison
Shakespeare's clearest use of dialect for sociolinguistic reasons can be found in the play Henry V, where we meet the Welshman Captain Fluellen, the Scotsman Captain Jamy and the Irishman Captain Macmorris. But what might contemporary audiences have made of these Celtic characters? What popular understandings of Celtic identities did Shakespeare's characters trigger? Recent technological developments, largely in the domain of corpus linguistics, have enabled us to construct robust but nuanced answers to such questions. In this study, we use CQPweb, a corpus analysis tool developed by Andrew Hardie at Lancaster University, to explore Celtic identity terms in a corpus developed by the Encyclopedia of Shakespeare's Language Project. This corpus contains some 380 million words spanning the 80-year period 1560–1639 and allows us to tap into the attitudes and stereotypes that would have become entrenched in the years leading up to Henry V 's appearance in 1599. We will show how the words tending to co-occur with the words Scots/Scottish, Irish and Welsh reveal contemporary understandings of these identities. Results flowing from the analyses of collocates include the fact that the Irish were considered wild and savage, but also that the word Irish had one particular positive use – when modifying the word rug . In discussing our findings, we will take note of critical discussions, both present day and early modern, on 'nationhood' in relation to these characters and identities. We will also conduct, partly for contrastive purposes, a brief analysis of the English identity.